Small data : the tiny clues that uncover huge trends - Lindström, Martin, 1970- (New York (N.Y.) : St. Martin's press, 2016)
"Hired by the world's leading brands to find out what makes their customers tick, Martin Lindstrom spends 300 nights a year overseas, closely observing people in their homes. His goal: to uncover their hidden desires and turn them into breakthrough products for the world's leading brands. In a world besotted by the power of Big Data, he works like a modern-day Sherlock Holmes, accumulating small clues to help solve a stunningly diverse array of challenges. In Switzerland, a stuffed teddy bear in a teenage girl's bedroom helped revolutionize 1,000 stores, spread across twenty countries, for one of Europe's largest fashion retailers. In Dubai, a bracelet strung with pearls helped Jenny Craig offset its declining membership in the United States and increase loyalty by 159 percent in only a year. And in China, the look of a car dashboard led to the design of the Roomba vacuum - a great American success story. How? Lindstrom connects the dots in this globetrotting narrative that will fascinate not only marketers and brand managers, but anyone interested in the infinite variations of human behavior. The Desire Hunter combines armchair travel with forensic psychology into an interlocking series of international clue-gathering detective stories. It presents a rare behind-the-scenes look at what it takes to create global brands; and along the way, reveals surprising and counter-intuitive truths about what connects us all as humans"--
Includes bibliographical references (pages 235-239) and index.
Keywords: BUSINESS & ECONOMICS -- Consumer Behavior; BUSINESS & ECONOMICS -- Marketing -- General; Branding (Marketing).; Consumer behavior; Marketing -- Consumenten; Merken